Fabrication and Performance of Solid Oxide Fuel Cells with La0.2Sr0.7TiO3–δ as Anode Support and La2NiO4+δ as Cathode. Issue 6 (28th November 2016) - Li, S.; Tu, H.; Yu, L.; Anwar, M. T.
Abstract: A novel fabrication process for solid oxide fuel cells (SOFCs) with La0.2 Sr0.7 TiO3– δ (LSTA –) as anode support and La2 NiO4+ δ (LNO) as cathode material, which avoids complicated impregnation process, is designed and investigated. The LSTA – anode‐supported half cells are reduced at 1, 200 °C in hydrogen atmosphere. Subsequently, the LNO cathode is sintered on the YSZ electrolyte at 1, 200 °C in nitrogen atmosphere and then annealed in situ at 850 °C in air. The results of XRD analysis and electrical conductivity measurement indicate that the structure and electrochemical characteristics of LNO appear similar before and after the sintering processes of the cathode. By using La0.6 Sr0.4 CoO3– δ (LSC) as current collector, the cell with LNO cathode sintered in nitrogen atmosphere exhibits the power density at 0.7 V of 235 mW cm −2 at 800 °C. The ohmic resistance (RS ) and polarization resistance (RP ) are 0.373 and 0.452 Ω cm 2, respectively. Compared to that of the cell with the LNO cathode sintered in air, the sintering processes of the cell with the LNO cathode sintered in nitrogen atmosphere can result in better electrochemical performance of the cell mainly due to the decrease in RS . The microstructures of the cells reveal a good adhesion between each layer.